Safety of once-or twice-daily dosing of non-vitamin K antagonist oral anticoagulants (NOACs) in patients with nonvalvular atrial fibrillation: A NOAC-TR study - Emren, Sadik Volkan; Zoghi, Mehdi; Berilgen, Rida; Ozdemir, Ibrahim Halil; Celik, Oguzhan; Cetin, Nurullah; Ergene, Oktay (Assoc Basic Medical Sci Federation Bosnia & Herzegovina Sarajevo, 2018)
Once-daily dosing of non-vitamin K antagonist oral anticoagulants (NOACs) may increase patient adherence to treatment but may also be associated with a higher risk of bleeding. In this study, we investigated the adherence to once-or twice-daily dosing of NOACs and the risk of bleeding in nonvalvular atrial fibrillation (NVAF) patients. This multicenter cross-sectional study, conducted between 1 September 2015 and 28 February 2016, included 2214 patients receiving NOACs for at least 3 months, due to NVAF. Patients receiving once-daily or twice-daily NOAC doses were 1: 1 propensity score matched for baseline demographic characteristics and the presence of other diseases. The medication adherence was assessed by the 8-item Morisky Medication Adherence Scale. Risk factors were investigated in relation to minor and major bleeding. The mean age of patients was 71 +/- 10 years, and 53% of the patients were women. The medication adherence was lower in patients receiving twice-daily NOAC doses compared to once-daily-dose group (47% versus 53%, p = 0.001), and there was no difference between the groups in terms of minor (15% versus 16%, p = 0.292) and major bleeding (3% versus 3%, p = 0.796). Independent risk factors for bleeding were non-adherence to medication (OR: 1.62, 95% CI: 1.23-2.14, p = 0.001), presence of 3 or more other diseases (OR: 10.3, 95% CI: 5.3-20.3, p < 0.001), and HAS-BLED (Hypertension, Abnormal renal and liver function, Stroke, Bleeding, Labile INR, Elderly, Drugs or alcohol) score (OR: 4.84, 95% CI: 4.04-5.8, p < 0.001). In summary, the once-daily dose of NOACs was associated with increased patient adherence to medication, while it was not associated with bleeding complications.
Keywords: Daily dosing; bleeding; medication adherence; non-vitamin K antagonist oral anticoagulants; self-report; NOACs; nonvalvular atrial fibrillation; NVAF